2023
DOI: 10.1007/s11739-023-03447-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative research assessment: using metrics against gamed metrics

John P. A. Ioannidis,
Zacharias Maniadis

Abstract: Quantitative bibliometric indicators are widely used and widely misused for research assessments. Some metrics have acquired major importance in shaping and rewarding the careers of millions of scientists. Given their perceived prestige, they may be widely gamed in the current “publish or perish” or “get cited or perish” environment. This review examines several gaming practices, including authorship-based, citation-based, editorial-based, and journal-based gaming as well as gaming with outright fabrication. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…However, in the current ecosystem, citation counts are not an unbiased measure of impact. Therefore, as part of the metric, citation counts should be taken into after screening for fraudulent highly cited scientists, or by using metrics against gamed metrics (Ioannidis & Maniadis, 2024).…”
Section: Scientific Citations Are Biasedmentioning
confidence: 99%
“…However, in the current ecosystem, citation counts are not an unbiased measure of impact. Therefore, as part of the metric, citation counts should be taken into after screening for fraudulent highly cited scientists, or by using metrics against gamed metrics (Ioannidis & Maniadis, 2024).…”
Section: Scientific Citations Are Biasedmentioning
confidence: 99%
“…A 2012 paper that investigated retractions of drug therapy studies found that 72% of the retractions were due to research misconduct (Samp et al, 2012). Evaluation of scientists based on their publications and citations for career advancement is one of the incentives for the publication of fraudcontaining articles (Ioannidis & Maniadis, 2024). Interestingly, a number of authors have been associated with more than one retraction (Kuroki & Ukawa, 2018;Samp et al, 2012) and this has been designated as "serial cases of fraud", by Samp et al (2012).…”
mentioning
confidence: 99%
“…Regardless of the exact of mix of genuinely high output, spurious authorship standards, and outright unethical research practices (Ioannidis & Maniadis, 2024), extreme publishing authors appear to enjoy high success in terms in citation impact, especially when raw citation counts are considered. 44% of the most-cited authors across science in terms of raw citations are extreme publishing authors.…”
mentioning
confidence: 99%
“…However, this may be a bad idea as it may further exaggerate publication bias and other selection biases. Instead, it may be more realistic and appropriate to monitor extreme publishing behaviors in centralized, standardized databases (Ioannidis & Maniadis, 2023), as we have done here. This monitoring should allow careful in-depth assessments of extreme patterns for single authors, teams, institutions, and countries.…”
mentioning
confidence: 99%